Better together than alone?: investigating dyadic compassion meditation in an experimental study - Schültke, Leonie; Warth, Marco; Alpers, Georg W.; Ditzen, Beate; Aguilar-Raab, Corina (Journal of social and personal relationships, 2023)
While meditation is commonly practiced by individuals on their own, several programmes have incorporated dyadic forms, too. However, the setting - meditating alone or in dyads - and its impact on the effects of meditation have not yet been examined. We expected that dyadic compassion meditation (CM) may improve perceived social closeness more compared to closely-matched individual CM. N = 50 couples were randomly assigned to do a brief 15-min CM induction either together with their partner or individually. Social closeness was rated by both partners. Secondary outcomes were positive and negative affect as well as parasympathetic response, indicated by heart rate variability (HRV). Due to the dyadic data structure, multilevel models were tested. We found no difference between dyadic and individual CM in self-report. After both forms social closeness and positive affect were improved, while negative affect decreased. Only HRV differed between the two conditions over time: while HRV significantly decreased in the individual condition, there was no such change in the dyadic condition. The accompanying physiological profile suggests that CM may involve effort at least in the individual CM. Done individually or with a partner, brief CM can foster social closeness and improve affect and can be employed to improve socio-emotional well-being.